PAYMENT OF REPLACEMENT MONEY AS AN EFFORT FOR RECOVERY OF STATE FINANCIAL LOSSES IN CRIMINAL ACTS OF CORRUPTION - I Wayan Sutije; Helmi Helmi; Mispansyah Mispansyah (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2023)
This study aims to analyze the implementation of Compensation Payments as an Effort to Recover State Financial Losses in Corruption Crimes paid by perpetrators of criminal acts in the future. This research uses a normative research method that is prescriptive in nature because it focuses on research on norms that prioritize legal materials in the form of library materials, examines legal principles, the legal system, and legal synchronization by analyzing them, using a statutory approach. and conceptual approach. The results of this study show that the payment of replacement money as an effort to recover state financial losses creates a dynamic that is quite complicated because it collides with normative rules that provide loopholes for convicts to undergo subsidiary crimes.Keywords: Replacement Money; Corruption; Child Crime